Cartão de visita: uma estratégia de marketing profissional na prática odontológica - Costa, Gabriela Magosteiro Viveiros Tabith [UNESP] (2015)
The objective of this study was to analyze the business cards used as the initial strategy of marketing Dentists, based on the Code of Dental Ethics, Law No. 5081 / 24/08/1966 and the principles of marketing. It is a cross-sectional study, which evaluated the 472 cards of Dental Clinics of Municipalities of Araçatuba, Region of São Paulo. Among the cards reviewed, based on the Code of Ethics, only 59.63% contained the registration number in the Regional Council of Dentistry, in 32.22% of the cards noted misuse of the term general practice, rather than GP. The item was on the cards unless found the specification of the profession Surgeon / Dental Surgeon (57.41%). According to Law No. 5081 / 1966, which regulates dentists, 37.22% of the cards improperly determined that the exercise more than two professional specialty; contained 19.26% of total ad price and terms of service payment. Thus, it appears that business cards are an important means of dissemination of professional work, but some Dentists have neglected ethical and legal principles. Thus, it emphasizes the need for awareness among professionals about the issues related to advertising and marketing